ОРГАНИЗАЦИЯ ЦЕНТРА ОБРАБОТКИ НАУЧНОЙ ИНФОРМАЦИИ ДЛЯ ПРОЕКТА РАДИОАСТРОН - Шацкая, М. В.; Андрианов, А. А.; Гирин, И. А.; Исаев, Е. А.; Костенко, В. И.; Лихачев, С. Ф.; Пимаков, А. С.; Селиверстов, С. И.; Федоров, Н. А. (Одеські астрономічні публікації, 2011)
—